Crime and Education - Stephen Machin; Matteo Sandi (CESifo GmbH, 2024)
Research studying connections between crime and education is a prominent aspect of the big increase of publication and research interest in the economics of crime field. This work demonstrates a crime reducing impact of education, which can be interpreted as causal through leveraging research designs (e.g., based on education policy changes) that ensure the direction of causality flows from education to crime. A significant body of research also explores in detail, and in various directions, the means by which education has a crime reducing impact. This includes evidence on incapacitation versus productivity raising aspects of education, and on the quality of schooling at different stages of education, ranging from early age interventions, through primary and secondary schooling and policy changes that alter school dropout age. From this evidence base, there are education policies that have been effective crime prevention tools in many settings around the world.
Keywords: K42; 330; crime; education